Investigation of lanthanum trioxypurine with zinc stearate and pentaerythritol as complex thermal stabilizers for poly(vinyl chloride). Issue 4 (22nd February 2019) - Ye, Feng; Ye, Qiufeng; Guo, Xiaojie; Zhan, Haihua; Fang, Cheng; Hu, Diefei; Mao, Qijing
Abstract : Lanthanum trioxypurine (LaTr) was triumphantly synthesized by reacting trioxypurine and lanthanum nitrate at neutral condition and was characterized by elemental analysis, Fourier transform infrared spectroscopy, and thermogravimetric analysis. The thermal stability effect of LaTr with its assistant thermal stabilizers about zinc stearate (ZnSt2 ) and pentaerythritol (Pe) on poly(vinyl chloride) (PVC) was investigated by Congo red test, discoloration test, UV–vis spectroscopy test, and thermal decomposition kinetics. The results showed that the addition of LaTr as thermal stabilizer could significantly enhance static stability time and long‐term stability of PVC. It could be mainly attributed to the anions in the structure of LaTr, could efficiently absorb the hydrogen chloride released by PVC, and have ability to replace unstable chlorine atoms on structure of PVC. Moreover, the mixing of LaTr, Pe, and ZnSt2 could reveal an excellent synergistic effect and both promote the initial color and the long‐term thermal stability of PVC. The thermal stability of PVC reached the optimal state when the ratio of LaTr/Pe/ZnSt2 was 1.8/0.6/0.6. In addition, compared with the reaction energy E a and UV–vis spectroscopy test's result of PVC samples, the order of PVC's thermal stability was PVC/LaTr/Pe/ZnSt2  > PVC/LaTr/Pe > PVC/LaTr. The result was further ascertained that LaTr/Pe/ZnSt2 showed excellent synergistic effect and could be used as an excellent complex thermal stabilizer for PVC. J. VINYL ADDIT. TECHNOL., 25:347–358, 2019. © 2019 Society of Plastics Engineers